Generating Series for Nested Bethe Vectors - Khoroshkin, S.; Pakuliak, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We reformulate nested relations between off-shell Uq(^glN) Bethe vectors as a certain equation on generating series of strings of the composed Uq(^glN) currents. Using inversion of the generating series we find a new type of hierarchical relations between universal off-shell Bethe vectors, useful for a derivation of Bethe equation. As an example of application, we use these relations for a derivation of analytical Bethe ansatz equations [Arnaudon D. et al., Ann. Henri Poincaré 7 (2006), 1217-1268, math-ph/0512037] for the parameters of universal Bethe vectors of the algebra Uq(^gl2).